Health insurance policy enforcement and catastrophic health expenditure: a case study in Sichuan province, China - Liu, Wei; Huang, Guowu (Frontiers in Public Health, 2025)
IntroductionChina’s health insurance reforms aim for universal coverage and financial relief, but implementation varies by region, urban–rural areas, and ethnic groups, highlighting disparities in healthcare access and socioeconomic status. Yet, the specific impact of policy enforcement deviations on catastrophic health expenditure remains underexplored, particularly amid China’s urban–rural and ethnic diversity.MethodsOur study is based on survey data of urban and rural residents’ medical insurance in Chengdu, Zigong, Nanchong, Aba Tibetan, Qiang Autonomous Prefecture, and Liangshan Yi Autonomous Prefecture of Sichuan Province (N = 1,460), exploring the impact of deviations in health insurance policy enforcement (DPE) on catastrophic health expenditure (CHE).ResultsBy constructing a binary probit model, instrumental variable method, and heterogeneity test, the study finds that DPE significantly increases the risk of households experiencing CHE, with each unit increase in the degree of deviation raising the probability of CHE by 7.45%. These risks are particularly pronounced in rural areas (p < 0.05), ethnic minority settlements (p < 0.01, p < 0.05), and the insured population (p < 0.05), with clear superimposed effects of economic vulnerability and cultural differences. Further analysis indicates that residents’ preferences for healthcare institutions (PHI) mediate between DPE and CHE, with policy execution deviations indirectly increasing the medical burden by inducing residents to choose higher-level healthcare institutions.DiscussionDrawing from empirical findings, we suggest enhancements in three areas: standardizing grassroots policy implementation, refining financing mechanisms, and advancing payment reforms to effectively mitigate CHE risks. Our study offers empirical support for improving the execution of medical insurance policies and driving reforms in healthcare systems, particularly by providing policy insights related to urban–rural integration and rural revitalization.